2014
DOI: 10.1007/978-3-319-07983-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Ontology Translation: A Case Study on Translating the Gene Ontology from English to German

Abstract: For many researchers, the purpose of ontologies is sharing data. This sharing is facilitated when ontologies are available in multiple languages, but inhibited when an ontology is only available in a single language. Ontologies should be accessible to people in multiple languages, since multilingualism is inevitable in any scientific work. Due to resource scarcity, most ontologies of the biomedical domain are available only in English at present. We present techniques to translate Gene Ontology terms from Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The results of this work may not be generalized to all types of entities. Hailu et al (2014) have found equivalent results for the translation of the Gene Ontology between English and German, but Silva et al (2015) did not find the same results on their partial translation of MeSH.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The results of this work may not be generalized to all types of entities. Hailu et al (2014) have found equivalent results for the translation of the Gene Ontology between English and German, but Silva et al (2015) did not find the same results on their partial translation of MeSH.…”
Section: Discussionmentioning
confidence: 96%
“…We also go further than these firstorder links and explore the possibility of using secondorder links to improve the coverage of the mappings between the sources. Compared to the same works, we also present a more complete study, Hailu et al (2014) only evaluate on 75 terms and Silva et al (2015) on 191 terms. We compare the coverage and quality of the entire biomedical ontology containing 10,444 terms.…”
Section: Resources and Related Workmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent study suggests automated translation services, like Google Translate, may begin to be efficient tools for medical translation, as they were able to extract consistent translations and data from Latin-based language manuscripts [13]. Google Translate was also used to provide an effective translation of the Gene Ontology from English to German [14]. The Global Public Health Intelligence Network (GPHIN) was designed to process data from news sources across the globe and uses automated translation across nine languages to provide aggregate information regarding disease outbreaks [15].…”
Section: Discussionmentioning
confidence: 99%